S48 Continuous positive airway pressure titration in awake obese subjects with obstructive sleep apnoea and its impact on neural respiratory drive and breathlessness. (12th November 2015) - Xiao, S; Bastianpillai, J; Ratneswaran, C; Pengo, M; Luo, YM; Jolley, CJ; Moxham, J; Steier, J
Abstract : Background: Continuous positive airway pressure (CPAP) is an effective treatment for obstructive sleep apnoea (OSA). We assessed neural respiratory drive (NRD), as measured by the surface electromyogram of the parasternal intercostals (sEMGpara ), during awake CPAP titration to quantify the effect of chest inflation on the load of the respiratory system. Patients and methods: Obese patients (body-mass-index, BMI >30) with confirmed obstructive sleep apnoea (OSA) were studied and NRD (sEMGpara ) and the surface EMG of the external oblique (sEMGabd ) were recorded and normalised to baseline activity (awake, supine). The apnoea-hypopnoea index (AHI) and 95 th percentile of CPAP were determined in sleep studies. The patients were then studied whilst awake and breathing on CPAP (4–20 cmH2 O, increments of 2 cmH2 O/3 mins), with the modified Borg score (mBorg) recorded. Results: 15 patients (age 48 ± 10 years, 12 male, BMI 38.9 ± 5.8) suffering with moderate-severe OSA (AHI 32.2 ± 21.1/h, 95 th percentile nocturnal CPAP 14.1 ± 3.8 cmH2 O) were studied. Awake, sEMGpara declined by 15.1 ± 1.5% from baseline when CPAP was applied, with the nadir at a CPAP of 10.6 ± 3.4 cmH2 O (p = 0.026). Further increase in CPAP levels led to a rise in sEMGpara and breathlessness (mBorg at lowest sEMGpara 0.9 ± 0.8 points, at CPAP of 20 cmH2 O 2.7 ± 2.7 points, p = 0.02). Conclusion: The respiratory system is maximally offloaded with subtherapeutic CPAP levels in OSA. Levels of NRD observed at effective CPAP levels are associated with breathlessness which can impact on CPAP compliance.